ISLAM DAN NEGARA - Ridha Amalia; Fitri Rahmadani; Dahlan Lama Bawa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the concepts of Islam and the state and various perspectives on their relationship. The research method used is library research with a qualitative-descriptive approach, through a review of books, scientific journals, articles, and documents relevant to the research theme. The results of the discussion indicate that Islam and the state are interrelated and complementary, with Islam serving as a source of values, morals, and ethical guidelines in social and political life, while the state serves as a means to regulate and realize welfare, justice, and social well-being without having to completely merge religion and state.